Headache characteristics and postoperative course in Chiari I malformation. (August 2022) - Thunstedt, Dennis C; Schmutzer, Michael; Fabritius, Matthias P; Thorsteinsdottir, Jun; Kunz, Mathias; Ruscheweyh, Ruth; Straube, Andreas
Background: Chiari I malformation typically presents with cough headache. However, migraine-like or tension-type-like headaches may also occur. There are limited publications on Chiari I malformation-associated headache semiologies and the effect of foramen magnum decompression on different headache types. Methods: A retrospective analysis complemented by structured phone interviews was performed on 65 patients with Chiari I malformation, treated at our hospital between 2010 and 2021. Headache semiology (according to ICHD-3), frequency, intensity, and radiological characteristics were evaluated pre- and postoperatively. Results: We included 65 patients. 38 patients were female and 27 male. Mean age was 43.9 ± 15.7 years. Headache was predominant in 41 patients (63.0%). Twenty-one patients had cough headache and 20 had atypical headache (12 migrainous, eight tension-type headache-like). Thirty-five patients with headache underwent surgery. Frequency, intensity, and analgesic use was significantly reduced in cough headache ( p < 0.001). Atypical headaches improved less ( p = 0.004 to 0.176). Exploratory analysis suggested that larger preoperative tonsillar descent correlated with larger postoperative headache intensity relief ( p = 0.025). Conclusion: Decompression was effective in Chiari I malformation-related cough headache. Atypical headache responded less well, and the causal relation with Chiari I malformation remains uncertain. For atypical headache, decompression should only be considered after failed appropriate preventive therapy and within an interdisciplinary approach involving a neurologist.